RETRACTED: Perbedaan Pengaruh Metode Latihan Plyometric Terhadap Peningkatan Power Otot Tungkai Pesilat Tapak Suci - Eko Sudarmanto; Agung Pipit Supriyadi; M Idzhar Hakiki (JUARA : Jurnal Olahraga, 2019)
This article has been retracted at the request of the Editor-in-Chief. Please see JUARA: Jurnal Olahraga Policy on Article Withdrawal (http://jurnal.upmk.ac.id/index.php/juara/Plagiarism_Retracted).Reason: This article contains some duplicate material of a paper that was originally published in proceedings of the 2018 National Education Seminar (http://hdl.handle.net/11617/10553)One of the conditions of submission of a paper for publication is that authors declare explicitly that all of their work is original and has not appeared in a publication elsewhere. We apologize to readers of the journal that this was not detected during the submission process.